Linkages Between External Debt Data and Balance of Payments, Government Finance and Monetary Statistics - Bove, Jan (IMF Working Papers; Working Paper ;, 1992)
This paper examines the linkages between key macroeconomic statistics: external debt, balance of payments, government finance, and monetary statistics, which enable analysts and policy makers to monitor economic developments. The paper reviews statistical compilation issues and concludes that, while considerable progress has been made in recent years to account for external debt and related flows, further progress must be made. It makes recommendations, such as improved communication among compilers of related statistics, that may help compilers to achieve greater consistency between statistics concerned and thereby enhancing their usefulness for analysts and policy makers. The need for increased resources to develop statistical systems is also recognized.